2010 IEEE International Conference on Communications 2010
DOI: 10.1109/icc.2010.5502293
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Decoding Algorithm for the Davey-MacKay Construction

Abstract: Abstract-The Deletion-Insertion Correcting Code construction proposed by Davey and MacKay consists of an inner code that recovers synchronization and an outer code that provides substitution error protection. The inner code uses low-weight codewords which are added (modulo two) to a pilot sequence. The receiver is able to synchronise on the pilot sequence in spite of the changes introduced by the added codeword.The original bit-level formulation of the inner decoder assumes that all bits in the sparse codebook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 7 publications
2
51
0
Order By: Relevance
“…While this assumption clearly gives some mismatch at the receiver, a reliable estimator has still not been developed for this channel. Unlike the simulations published in [9], we do not put a limit on the burst length I of insertions, resulting in a small improvement on decoding performance. When applied to the output of the watermark decoder, we have observed that the best response is obtained if the received sequence is truncated to 3 000 bits before decoding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While this assumption clearly gives some mismatch at the receiver, a reliable estimator has still not been developed for this channel. Unlike the simulations published in [9], we do not put a limit on the burst length I of insertions, resulting in a small improvement on decoding performance. When applied to the output of the watermark decoder, we have observed that the best response is obtained if the received sequence is truncated to 3 000 bits before decoding.…”
Section: Resultsmentioning
confidence: 99%
“…2) Outer Codes: As outer codes, we use a parallel concatenation of non-binary constituent codes, as presented in [9]. The constituent code is defined over an unterminated trellis, and an S-random interleaver [11] of block size K = 75 and spread S = 7.…”
Section: ) Inner Codesmentioning
confidence: 99%
See 2 more Smart Citations
“…An optimal symbol-level decoding algorithm was presented in [8] for the DM inner code; at the same decoding complexity, the new decoder takes sums over each possible sparse symbol when determining synchronization. This has two principal advantages: a) it allows the decoder to make use of a priori information for the sparsely-represented symbols, and b) it allows the use of non-sparse representations of the message.…”
Section: Introductionmentioning
confidence: 99%